Induction of anaesthesia with propofol according to the adjusted ideal body mass in obese and non-obese patients: an observational study. (2nd January 2019) - Smith, FJ; Jurgens, FX; Coetzee, JF; Becker, PJ
Abstract : Background: Obesity changes body composition including fat free mass (FFM), regarded as the "pharmacologically active mass". Scaling drug doses to obese patients by total body mass (TBM) results in overdose. We aimed to determine the success rate of inducing anaesthesia in normal, overweight and obese patients with propofol, using an adjusted body mass scalar (ABM), which embodies the increased FFM of obese patients. Methods: Ninety-six patients were divided into three groups according to body mass index (BMI): normal, overweight and obese. Propofol 2 mg/kg ABM was administered according to the equation: ABM = IBM + 0.4(TBM – IBM), where IBM = ideal body mass. Induction success was assessed clinically and by electroencephalographic spectral entropy. Results: The groups were similar regarding gender, age, height and IBM. One patient was morbidly obese (BMI = 44). State entropy (SE) decreased to < 60 in 33/33, 28/29 and 33/34 patients in the normal-weight, overweight and obese groups respectively, an overall success rate of 97.5% (95% confidence interval 92.7% to 99.4%). Median lowest achieved SE values and median times that SE remained < 60 did not differ between groups, however the individual values ranged widely in all three groups. Induction failed in the two patients whose SE did not decrease to < 60 (one overweight and one obese). Conclusions: The ABM-based propofol induction dose has a high success rate in normal, overweight and obese patients. Further studies are required to determine the feasibility among morbidly obese patients.